Maintenance strategies and life-cycle cost analysis of inspection robots in metro tunnels - Chen, Xin; Zhang, Qingsong; Liu, Rentai; Wang, Xiaofeng; He, Wanli (Tunnelling and underground space technology, 2023)
[Display omitted] •A life-cycle cost calculation method for inspection subject is proposed.•The relationship between inspection accuracy and inspection cycle is explored.•The detection accuracy interval of inspection robot in low cost operation is proposed.•A reasonable index interval before the inspection robot is put into use is proposed. Inspection robots are rarely employed in metro tunnels. This is related to the fact that the various technical indicators of inspection robots are not balanced under the existing technical conditions. This study proposes a method for developing a maintenance strategy and assessing the life-cycle cost of inspection robots in metro tunnels to determine whether they should be used. A tunnel structure deterioration model based on a non-stationary gamma process was used. Based on this, a life-cycle costing model for a tunnel inspection strategy was designed. This model considers the accuracy of inspection subject, inspection cycle, cost of attendance, and maximum mileage and achieves a good assessment of the inspection subject. The study shows that the inspection cycle has a non-linear relationship with the life-cycle cost and that the inspection cycle has a minimum cost range. The detection accuracy of the inspection subject is negatively correlated with the life-cycle cost. However, when the detection accuracy reached 71%, the life-cycle cost was only 5% higher than the minimum cost, which is a good result for low operating costs. An evaluation model of the inspection indices under the combined effect of departure cost d, maximum mileage m, inspection accuracy pi and probability of failure pf of the inspection robot was established to guide its intervention indexes.